Kesesuaian antara Fatwa Yusuf Qardhawi dan KHI terkait Wali Mujbir dan Wali Nikah - Yusrizal, Navis (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
There are divisions, friction and disagreements in the household that reach the divorce line. Usually, these things are caused by incompatibility between the husband and wife; one of the causes is forced marriage or mujbir guardian. Ulama also has different opinions regarding the marriage guardian and the mujbir guardian. This research examines Yusuf Qardhawi's fatwa and its relevance to KHI. There are three formulations for this research, namely: What is Yusuf Qardhawi's view of mujbir guardian and marriage guardian? and what is their relevance to KHI? the method researchers chose here is library research with a qualitative approach. Data sources include primary data from Yusuf Qardhawi's fatwa and KHI. Meanwhile, secondary data is in fiqh books, journals and others. From the analysis that the author has carried out, Yusuf Qardhawi rejects the opinion that allows guardians forced on girls because several hadiths require consultation with girls when they want to get married, so the sign is that they are not allowed to marry without their consent, and also have to look at the historical framework in Imam Syafi'i's era where women did not have the ability to choose a partner, is different from this era where women's education is equal to that of men. Yusuf Qardhawi's opinion is relevant to KHI article 16, paragraph 1. Yusuf Qardhawi also allows marriage without a guardian, as is Hanafi opinion; this is not relevant to KHI in article 14, which makes the guardian one of the pillars.